"Hey, You Stylized Woman There": An Uncomfortable Reflexive Account of Performative Practices in the Field. (June 2015) - Dosekun, Simidele
This article presents an uncomfortable reflexive account of a feminist poststructuralist research project on young women in Lagos, Nigeria who dress in what I call "hyper-feminine style." It reflects on the messy processes by which I framed the research and recruited participants, and considers how the women who did or did not eventually take part exercised agency to resist the terms of my address. The article illustrates the usefulness of Butler's theoretical notions of "excitable discourse" and "performative interpellation" for poststructuralist reflexive practice, concerning as they do the unpredictable political and ontological effects of what one says and does.